Karakteristik Pati Talas Banten yang Dimodifikasi Menggunakan Asetat Anhidrida - Ahmad Wibisana; Dewi Nurul Aulia; Siti Nurhidayah; Dewi Hisi Anggaraeni; Fischar Chicko (Jurnal Ilmiah Teknik Kimia, 2022)
Taro beneng (Xanthosoma undipes k.koch) is a tuber plant originating from Pandeglang. Taro tubers have a high starch content so they are the potential to be used in various industrial applications such as in the fields of food, textiles, paper, and others. In general, the use of natural starch for the industry has disadvantages related to its Physico-chemical characteristics. For a wider application, starch needs to be modified in order to have certain characteristics that are suitable for a certain application. In this study, a starch modification was carried out by the acetylation method using acetic anhydride. The independent variables used in this study were the ratio of acetic anhydride/dry starch (g/g): 0, 5, 10, 20%, while the dependent variables were % acetyl, degree of acetylation, swelling power, and solubility. The acetylation reaction was carried out at 35°C for 30 minutes. The results showed that starch acetylation using an acetic anhydride/starch ratio of 10 g/50 g resulted in percent acetylation (% acetyl) and degree of substitution (DS) were 4.3% and 0.16%, respectively. The highest swelling power value was 5.2 g/g, while the highest acetyl starch solubility was 1.6% which was obtained on acetylation using an acetic anhydride/starch ratio of 5/50 g/g.